2011
DOI: 10.1089/aid.2010.0205
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Development of Antiretroviral Drug Resistance Mutations in HIV-Infected Children Less Than Two Years of Age Initiating Protease Inhibitor-Based Therapy in South Africa

Abstract: Data on the development of antiretroviral drug resistance in HIV-1-infected children receiving protease inhibitor (PI)-based antiretroviral therapy (ART) are limited. We examined antiretroviral resistance among a cohort of 323 South African HIV-infected children < 2 years old exposed to nevirapine for prevention of mother-to-child transmission. Ritonavir (RTV) was used initially for 138 children who were < 6 months old or receiving antimycobacterial therapy; otherwise children received lopinavir/ritonavir (LPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 40 publications
(46 reference statements)
11
28
0
Order By: Relevance
“…We found PI mutations in 73% of genotypes, substantially higher than the 17% to 44% reported in previous South African studies of children failing PI regimens, although these earlier studies included children on LPV/r-regimens in addition to RTV-sPI-regimens. 7,17,18 In Brazil, almost half of the children on either RTV-sPI or nelfinavir-based ART had PI mutations, 19 while in another South African study, major PI mutations were found in 71% of children with treatment failure and prior RTV-sPI exposure, a result that is very similar to the present findings. 10 The intriguing finding that use of PI-regimens is protective against development of resistance against co-administered antiretroviral drugs has been described in adults in relation to the M184V and K65R mutations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found PI mutations in 73% of genotypes, substantially higher than the 17% to 44% reported in previous South African studies of children failing PI regimens, although these earlier studies included children on LPV/r-regimens in addition to RTV-sPI-regimens. 7,17,18 In Brazil, almost half of the children on either RTV-sPI or nelfinavir-based ART had PI mutations, 19 while in another South African study, major PI mutations were found in 71% of children with treatment failure and prior RTV-sPI exposure, a result that is very similar to the present findings. 10 The intriguing finding that use of PI-regimens is protective against development of resistance against co-administered antiretroviral drugs has been described in adults in relation to the M184V and K65R mutations.…”
Section: Discussionsupporting
confidence: 88%
“…6,18 ART drug classes and drugs themselves have different genetic barriers to resistance. Lamivudine and the NNRTIs, for example, have a low barrier to resistance, with a single mutation enough to confer complete resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that, in young children for whom LPV/r-based regimens have failed, selection of major mutations to PI is rare and accumulation of thymidine analogue mutations is very limited (156,237,239,240). In this context and in the absence of robust second-line alternatives such as DRV/r-containing regimens, the Guidelines Development Group recommended that children younger than three years of age should be maintained on LPV/r until the age of three years, despite treatment failure.…”
Section: Rationale and Supporting Evidencementioning
confidence: 99%
“…The recommendations are now better informed by paediatric clinical trial data (156,158,237) and observational data (157). The Guidelines Development Group also considered operational and programmatic issues including the availability of heat-stable formulations and fixed-dose combinations for children.…”
Section: Introductionmentioning
confidence: 99%
“…Children failing LPV/r rarely have LPV/r resistance initially, unless previously given RTV monotherapy or TB therapy. [33,34] In children failing LPV/r as a first regimen, a resistance test and possibly LPV/r trough levels should be considered. We need more data on hair levels of LPV/r as a measure of long-term adherence before this strategy can be recommended.…”
Section: Failure Of First-line Regimensmentioning
confidence: 99%